Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper analyzes the current account performance of Denmark in 1993-98. The paper presents a brief review of structural features of the external current account. It looks at the decline in export market share and concludes that it reflects primarily cyclical factors and the unwinding of an unsustainable export market gain immediately after the German unification. The paper also examines implications for fiscal policy of Denmark's decision to remain for the time being outside the European Monetary Union.